MEMBRAN KERAMIK MANGANESE GREENSAND DAPAT MENURUNKAN TOTAL COLIFORM PADA AIR BERSIH - Rifda Aulia; Irmawartini; Agus Somad Saputra (Jurnal Kesehatan Siliwangi, 2021)
Total Coliform in clean water is harmful to health if it exceeds the quality standard. The total Coliform in the clean water examined was 81 APM/100 mL, which exceeds the quality standard based on the Regulation of the Minister of Health No. 32 of 2017. Ceramic membrane is a technology that can reduce Total Coliform in clean water. This technology can operate at low pressure, using natural materials such as clay and sawdust. The purpose of the study was to determine the effect of manganese greensand ceramic membranes on Total Coliform in clean water in the kitchen of PT. X. This research is a field-scale experimental study with a pretest – posttest without control design, using grab sampling technique and data analysis using the Wilcoxon test. The results of the study were the average percentage of total coliform reduction was 69.55% (composition 50:50) and 53.07% (composition 40:60). The average difference in Total Coliform is 16 CFU/100 mL (50:50 composition) and 13 CFU/100 mL (40:60 composition). The results of statistical analysis related to the effect of manganese greensand ceramic membranes on the number of Total Coliforms, namely the value of Sig. (50:50 composition) = 0.008 and (40:60 composition) = 0.017. The sig value is smaller than the value of (0.05), which means that there is an effect of manganese greensand ceramic membrane on the total coliform. Manganese greensand ceramic membrane can reduce Total Coliform and the composition variation of 50:50 is a variation that is better than the composition of 40:60.